A CD40/CD40L feedback loop drives the breakdown of CD8+ T‐cell tolerance following depletion of suppressive CD4+ T cells. Issue 4 (20th January 2014) - Muth, Sabine; Schütze, Kristian; Hain, Tobias; Yagita, Hideo; Schild, Hansjörg; Probst, Hans Christian
<x xml:space="preserve">Abstract</x> Dendritic cells (DCs) are the key APCs not only for the priming of naïve T cells, but also for the induction and maintenance of peripheral T‐cell tolerance. We have recently shown that cognate interactions between Foxp3+ Tregs and steady‐state DCs are crucial to maintain the tolerogenic potential of DCs. Using DIETER mice, which allow the induction of antigen presentation selectively on DCs without altering their maturation status, we show here that breakdown of CD8+ T‐cell tolerance, which ensues after depletion of suppressive CD4+ T cells, is driven by a positive feedback loop in which autoreactive CD8+ T cells activate DCs via CD40. These data identify ligation of CD40 on DCs as a stimulus that promotes autoreactive T‐cell priming when regulatory T‐cell suppression fails and suggest that feedback from autoreactive T cells to DCs may contribute to the well‐documented involvement of CD40 in many autoimmune diseases.